(untitled) (Вісник: Міжнародні відносини, 2025)
Introduction. Based on a retrospective analysis of the features, main priorities, and mechanisms for implementing the Middle East policy of the first administration of D. Trump, a prognostic analysis of US policy in the Middle East under the second administration of Donald Trump is created. Methods. General scientific and special research methods were used, in particular, a systemic approach, structural-functional analysis, comparative analysis, historical-comparative, and analytical-prognostic methods. Results. The conceptual, theoretical, and doctrinal foundations of D. Trump’s Middle East policy were identified and analyzed. The main means of implementing US geopolitical and geoeconomic interests in the Middle East were identified and an assessment of the effectiveness of these means and the degree of their correspondence to the manifestations of the goal was provided. The specification of the position of the D. Trump administration on the main regional problems is clarified, in particular, the fight against international terrorism, the Arab-Israeli and Palestinian-Israeli settlement, the Syrian crisis, the problem of non-proliferation of WMD. Conclusions. The leadership of the USA as a system-forming element of the Middle East regional system, which determined the main directions of the country’s movement in the region, is a thing of the past, they have not begun the main directions of its transformation, which is a consequence not so much of the influence of subjective and factors, but of objective processes of global regional transformations. It is proved that the Middle East policy of D. Trump is aimed at creating an optimal balance of power for the USA and manipulating it to ensure its own interests. The Middle East policy of the D. Trump administration will have a hereditary character and will be implemented during his second term in the White House.